Molluscan shellfish safety : proceedings of the 8th ICMSS, Charlottetown, PEI, Canada, June 12-17, 2011 - Sauve', Gilbert (New York : Springer, 2014)
In a time of rapid climatic, industrial and technological changes in molluscan shellfish producing and exporting regions, it is of the utmost importance to keep a keen eye on developing trends. This collection of recent research in molluscan shellfish safety, risk assessment, risk management, regulation and analytical methods presented at the 8th ICMSS (International Conference on Molluscan Shellfish Safety) offers valuable insights in the latest scientific findings
1. Management and regulation/gestion et la reglementation -- 2. Health risk assessment/evaluation de risques a la sante -- 3. Enteric viruses/virus enteriques -- 4. Chemical analytical methods/methodes d'analyse chimique -- 5. Chemical contaminants/polluants chimiques
Includes bibliographical references and index
Keywords: Mollusks -- Toxicology -- Congresses; Seafood poisoning -- Prevention -- Congresses; Shellfish as food -- Contamination -- Congresses